Breaking of seed dormancy in ash gourd (Benincasa pruriens) through fruit storage and seed treatments - SELVI, D THIRUSENDURA; SARASWATHY, S; AMBIKA, S; ABINAYA, K; KAVITHA, S; KAVITHA, P G; VIGNESHWARI, R; LAKSHMI, S (The Indian Journal of Agricultural Sciences, 2024)
The dormancy in seeds collected from freshly harvested ash gourd [Benincasa pruriens f. hispida (Thunb.) de Wilde & Duyfjes] fruits reduces the seed quality and field performance viz. early germination, faster seedling establishment and vigorous seedling growth. Post harvest storage of fruits and different physical and chemical methods are useful in breaking seed dormancy in cucurbits. The present study was carried out during winter (rabi) 2020–21 and rainy (kharif) seasons of 2021–22 at the Agricultural Research Station (Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu), Vaigai Dam, Tamil Nadu to identify the optimal duration of post-harvest fruit storage and dormancy-breaking method for reducing seed dormancy in ash gourd cv. CO 1. Experiment was conducted in a randomized block design (RBD) with 3 replications. Firstly, the results revealed that the seeds extracted from the fruits, which were stored for 60 days after harvest, exhibited the best field performance, viz. early emergence, higher field emergence, faster rate of emergence and more seedling length, seedling dry weight, seedling vigour index, and viability indicating that prolonged storage can effectively reduce seed dormancy. Secondly, among different dormancy-breaking treatments, warm stratification of seeds at 40–50°C for 5 days and soaking of seeds in 500 ppm ethrel for 16 h remarkably improved the field performance, indicating the usefulness of these methods in improving seed quality characteristics in ash gourd. Farmers can use ethrel to break dormancy in ash gourd.